2017
DOI: 10.1108/ajems-05-2016-0066
|View full text |Cite
|
Sign up to set email alerts
|

The leaders’ emotional intelligence

Abstract: Purpose The purpose of this paper is to determine the extent to which leaders’ emotional intelligence (EI) predict the voluntary work behaviors (i.e. organizational citizenship behavior (OCB) and counterproductive workplace behavior (CWB)) of employees in the Ghanaian banking sector. Design/methodology/approach Quantitative approach was adopted to collect data from 234 respondents working in both high- and low-performing banks in Ghana. Both purposive and simple random sampling techniques were used for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…Secondly, EI positively affects knowledge-sharing. This result is consistent with some previous studies of formula Dartey Baah et al [21], Polese et al [22], Tommasetti et al [23]. Acquisition of knowledge is done through the ability of individuals to perceive and process information, directly related to individual emotional factors such as emotional awareness and understanding [24].…”
Section: Results and Implicationssupporting
confidence: 91%
See 2 more Smart Citations
“…Secondly, EI positively affects knowledge-sharing. This result is consistent with some previous studies of formula Dartey Baah et al [21], Polese et al [22], Tommasetti et al [23]. Acquisition of knowledge is done through the ability of individuals to perceive and process information, directly related to individual emotional factors such as emotional awareness and understanding [24].…”
Section: Results and Implicationssupporting
confidence: 91%
“…After studying the studies of Dartey Baah et al [21], Polese et al [22], Tommasetti et al [23], Khalili, A. [27], Efthimiou [28], Callin and Bamford [20] the authors discovered the effect of the knowledge-sharing mediating factor in EI relationships and group work outcomes.…”
Section: Relationship Of Among Knowledge-sharing Ei and Group Work Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These skills are not different from those needed for relationship management, which is at the heart of employee engagement. This finding is consistent with that of Dartey-Baah and Mekpor (2017) who also concluded in their study on the Ghanaian banking industry that engaged employees were also emotionally intelligent.…”
Section: Co-worker Incivility: a Stressor Of Employeessupporting
confidence: 91%
“…Zulfadil et al [29] suggested that EI directly influences knowledge Sharing, conflict in teams, the structure mechanism, and team performance. Several previous studies [30][31][32][33][34][35][36] have found a partial relationship between EI and team performance. Regarding the relationship between EI and innovation, Blázquez and Bermúdez [37] empirically demonstrate that senior executives' EI exerts a positive, direct influence on innovation in Spanish companies.…”
Section: Theoretical Background 21 Emotional Intelligence and Innovmentioning
confidence: 85%